AN EXPLORATION OF THE IMPACT OF HOTEL FACILITIES ON EMPLOYEE MOTIVATION AND PERFORMANCE: AN INDONESIA CASE STUDY - Nadhira Sukmana Putri (School of Tourism, Universitas Ciputra Surabaya, 2021)
The purpose of this study is to examine the impact of staff facilities on employee motivation and performance by using a case-study of Oberoi Beach Resort – a five-star hotel situated in Lombok, Indonesia. This study begins with a review of the research background, aim, and objectives. The author then addressed issues in the hospitality industry and the importance of maintaining employee morale and productivity. Next, the main topics of this study, i.e. employee productivity & well-being, staff facilities, motivation, and performance were analyzed. Such topics were narrowed and established as the basis for primary research. Mixed-method approach was adopted to verify theories with acquired data. Despite several limitations, this research found that wages, events for staff, and medical-room are effective in motivating them to perform better and to stay with the brand. Additionally, training and development is the best tool for performance enhancement.